2015
DOI: 10.1080/10426914.2015.1025975
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Carbon Nanotubes from Carbon-Rich Fly Ash: Growth Parameters and Mechanism

Abstract: Fly ash is a byproduct, generated due to the use of heavy oil or coal as a fuel in power plants. Recently, carbon rich fly ash is found to have ideal compositions as a catalyst and precursor for carbon nanotubes (CNTs) growth by the chemical vapor deposition method. The existing methods have a limitation on producing CNTs in a large scale. In this work the parameters effecting the growth of CNTs of fly ash were investigate. These include temperature, gas pressure, growth time and gas flow rate. The produced sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…These values are consistent with reports where coal fly ash was used as support for synthesis of CNMs. [42,44] In this case, the authors reported I G /I D ratios of 1.35 and 1.4 when acetylene was used for CNMs synthesis at 750 ºC. In that study, the results had indicated that the materials had a high degree of wall graphitization suggesting good quality CNTs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…These values are consistent with reports where coal fly ash was used as support for synthesis of CNMs. [42,44] In this case, the authors reported I G /I D ratios of 1.35 and 1.4 when acetylene was used for CNMs synthesis at 750 ºC. In that study, the results had indicated that the materials had a high degree of wall graphitization suggesting good quality CNTs.…”
Section: Resultsmentioning
confidence: 93%
“…[25,26,42] If the intensity ratio of G and the D peaks (I G /I D ) is high, it indicates the degree of wall graphitization which gives quality CNTs/CNFs with low defects and high crystallinity. [42,44,54] In this study, the D band peaks of all materials are more prominent except for Mag-Cethy which suggested that the obtained CNMs consist of defects, however more graphitic due to the higher intensity ratios. The I G /I D intensity ratios of the CNMs grown on CFA using both ethylene and pyrolysis oil vapour are the same with the value of 1.18, as indicated in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…13 Saudi Arabian and Japanese CFA have also been used to synthesize undoped CNTs. 14,15 Similarly, Salah et al have optimised the synthesis parameters (temperature, gas pressure, growth times, and gas ow rates for the decomposition of C 2 H 2 in the presence of H 2 ) for the growth of undoped MWCNTs on carbon rich CFA by low pressure chemical vapour deposition (LPCVD). 14 However, to date the synthesis of heteroatom-doped (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…13 This solid waste carbon rich material is not yet tried to be utilized as a source for nanostructures production. Salah and his group 11,12 showed the conversion of this y ash into CNTs and utilized them for different applications. Further, they reported that pure carbon content in the oil y ash is high, which has been extensively evaluated for the conversion into nanostructures and utilized for variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that this important nanomaterial can be produced using the chemical vapor deposition (CVD) method by utilizing oil y ash as a catalyst and co-precursor in the same time. 11,12 This ash is available in huge quantities as a solid waste and has a good amount of unburned carbon, which is more than 80%. 13 This solid waste carbon rich material is not yet tried to be utilized as a source for nanostructures production.…”
Section: Introductionmentioning
confidence: 99%